2017
DOI: 10.1017/s1751731116002822
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CP concentration in the diet on urea kinetics and microbial usage of recycled urea in cattle: a meta-analysis

Abstract: In ruminants, urea recycling is considered an evolutionary advantage. The amount of urea recycled mainly depends of the nitrogen (N) intake and the amount of organic matter (OM) digested in the rumen. Because recycled N contributes to meeting microbial N requirements, accurate estimates of urea recycling can improve the understanding of efficiency of N utilization and N losses to the environment. The objective of this study was to evaluate urea kinetics and microbial usage of recycled urea N in ruminants using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 32 publications
0
21
0
2
Order By: Relevance
“…In our study, the CP difference of diets (11.0 and 12.5% DM) was much lower and, probably, this had a limited impact on urea influx. In a recent meta-analysis Batista et al (2017) studied the relationship between dietary CP levels and the rumen urea N entry rate in a data set of trials involving several cattle categories. According to such a model, the different CP intakes in the trial of Røjen et al (2011) caused a variation of approx.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the CP difference of diets (11.0 and 12.5% DM) was much lower and, probably, this had a limited impact on urea influx. In a recent meta-analysis Batista et al (2017) studied the relationship between dietary CP levels and the rumen urea N entry rate in a data set of trials involving several cattle categories. According to such a model, the different CP intakes in the trial of Røjen et al (2011) caused a variation of approx.…”
Section: Discussionmentioning
confidence: 99%
“…In line with Reynolds and Huntington (1988), Spek et al (2013b) observed that the fraction of total urea entry rate that returned to the GIT was negatively related to dietary protein content. Reports on this type of measurements allowed Reynolds and Kristensen (2008), and more recently Batista et al (2017), to demonstrate that GER accounts for almost the entire urea entry rate in systemic blood when dietary DM contains 8% or less CP.…”
Section: Nitrogen/urea Recyclingmentioning
confidence: 92%
“…The nitrogen recycling capacity of ruminants has been reported as the main biological mechanism that allows the use of infrequent supplementation [4]. This can be significant even when animals are fed medium-high quality forage [5]. Moreover, because the last trimester of gestation usually coincides with the dry season and, postpartum interval plays an important role in determining a primiparous cow's calving interval in tropical conditions, producers are usually oriented to supplement cows at first and last trimester of gestation [6].…”
mentioning
confidence: 99%